(untitled) (International conference on multidisciplinary science, 2024)
To rear winter wheat in typical virgin land of Samarkand region which was encountered with irrigation erosion we recommend to use the way of treating land in boundary way. We advise to use the phosphoric fertilizer P2O5 differential application on the background of N200 and K 100 kg/ha in the not washed soil P2O5 , in the deeply washed part 140 kg/ha P2O5, and at the land where the flow gather 60kg/ha P2O5. With the help of this, the root system of the winter wheat grows strongly and it decreases the process of washing off the soil and feeding elements up to 28 – 32%. There are possibilities of getting high (52, 6- 56, 8) and good quality crop from all the parts of the land.